Evaluasi Keselamatan Alat Permainan Edukatif (APE) dan Penataan Area Bermain Outdoor di Dua Taman Kanak-Kanak - Willyado, Auri; Novrikasari, Novrikasari; Lestari, Mona; Waldani, Dina; Andarini, Desheila (National Journal of Occupational Health and Safety, 2025)
Educational Play Equipment (APE) is one of the facilities provided by Early Childhood Education (PAUD) institutions to support the learning process through play. This study aims to assess the compliance of APE and the arrangement of outdoor play areas with the 2018 Guidelines for Managing PAUD Classroom Space, SNI 9169:2023, the Ministry of Education and Culture’s 2021 Safe APE Guidelines for Early Childhood, and Ministerial Regulation No. 3 of 2022. The study employs a qualitative design with a descriptive approach through facility observations, interviews with teaching staff, and a review of school documents. The data analysis process includes data reduction, data presentation, and drawing conclusions. The findings indicate that Kindergartens X and Y have not fully met the required safety standards. Both schools still show insufficient attention to the stability of playground equipment, and several materials used may pose potential hazards to children. Such conditions can increase the risk of accidents in the play area, including bumps, falls, pinching injuries, and cuts. Therefore, repairs and replacements of unsafe equipment, rearrangement of play structures, improvements to the play surface using softer materials, and strengthened supervision by teachers and parents are needed to reduce the risk of injury. With these measures, children can play in an environment that is safer and minimizes potential hazards. Keywords: Educational Play Equipment, Play Area, Early Childhood Education, Occupational Safety, Child Safety